2018
DOI: 10.1016/j.fertnstert.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Differential rate in decline in ovarian reserve markers in women with polycystic ovary syndrome compared with control subjects: results of a longitudinal study

Abstract: Ovarian aging in PCOS is characterized by a more rapid decline in AMH and a slower decline in OV compared with control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The age-related decline in ovarian features, such as FNPO and OV, has been well documented in control women with normal reproductive health (20). Recently, two studies using longitudinal designs have documented the decline in ovarian parameters in women with PCOS and controls using measurements from a single plane (21) or whole ovary (22). Given the known decline in both FNPO and OV with aging, we hypothesized that accounting for age in the ovarian ultrasound thresholds would provide improved diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The age-related decline in ovarian features, such as FNPO and OV, has been well documented in control women with normal reproductive health (20). Recently, two studies using longitudinal designs have documented the decline in ovarian parameters in women with PCOS and controls using measurements from a single plane (21) or whole ovary (22). Given the known decline in both FNPO and OV with aging, we hypothesized that accounting for age in the ovarian ultrasound thresholds would provide improved diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating AMH levels in T-exposed monkeys, however, do not exceed those of controls, and exhibit an exaggerated, age-related decline [143]. While absence of AMH excess is atypical for women with PCOS, PCOS women over 30 years of age demonstrate a steeper decline in circulating AMH levels than their non-PCOS counterparts [144]. Early-to-mid gestation T reprogramming of ovarian follicle granulosa cells may therefore be less pronounced than ovarian theca, stroma or oocytes, and an extra-ovarian source of fetal hyperandrogenism, alone, may be insufficient to reprogram granulosa cell AMH hypersecretion or increase follicle number and proliferation.…”
Section: Nonhuman Female Primatesmentioning
confidence: 92%
“…This suggests that the inclusion of young women with PCOS with higher serum AMH levels contributed partly to the accelerated decrease in serum AMH with age in the infertile group. Also, previous studies reported that women with PCOS have an accelerated decrease in serum AMH with age compared to non-PCOS controls [28,29].…”
Section: Discussionmentioning
confidence: 88%